Monetary policy with model uncertainty: distribution forecast targeting - Lars E. O. Svensson; Noah Williams (Deutsche Bundesbank, 2005)
We examine optimal and other monetary policies in a linear-quadratic setup with a relatively general form of model uncertainty, so-called Markov jump-linear-quadratic systems extended to include forward-looking variables. The form of model uncertainty our framework encompasses includes : simple i.i.d. model deviations; serially correlated model deviations; estimable regimeswitching models; more complex structural uncertainty about very different models, for instance, backward- and forward-looking models; time-varying central-bank judgment about the state of model uncertainty; and so forth. We provide an algorithm for finding the optimal policy as well as solutions for arbitrary policy functions. This allows us to compute and plot consistent distribution forecasts "fan charts" of target variables and instruments. Our methods hence extend certainty equivalence and "mean forecast targeting" to more general certainty non-equivalence and "distribution forecast targeting."
Keywords: E52; E42; E58; 330; Optimal policy; multiplicative uncertainty; Geldpolitik; Risiko; Ökonometrisches Makromodell; Prognoseverfahren; Theorie